Penjabaran Nilai-Nilai Pluralisme Perspektif Nurcholish Madjid dalam Konteks Pendidikan Islam Multikultural - Jayana, Thoriq Aziz; Siswanto, Siswanto (Tarbawiyah Jurnal Ilmiah Pendidikan, 2022)
Plural-multicultural-based Islamic education becomes very urgent in its implementation to compensate for the reality of plurality. Nurcholish Madjid is one of the figures who are very vociferous in voicing the idea of pluralism, but it takes a strong reading/analysis in describing his ideas. This research includes a literature review with a content analysis method with hermeneutics. The results showed that the idea of Nurcholish pluralism can be described in seven main themes, namely the themes of tolerance, democracy, justice, humanity, equality of degrees, brotherhood, and local cultural wisdom with their own peculiarities. These themes are very important to be implemented in Islamic education to create a multicultural-based Islamic education.